Inheritance and innovation of the diagnosis of peripheral pulmonary lesions - Yang Xia; Qin Li; Changgao Zhong; Kopen Wang; Shiyue Li (SAGE Publishing, 2023)
As the leading cause of cancer-related deaths worldwide, early detection and diagnosis are crucial to reduce the mortality of lung cancer. To date, the diagnosis of the peripheral pulmonary lesions (PPLs) remains a major unmet clinical need. The urgency of diagnosing PPLs has driven a series of development of the advanced bronchoscopy-guided techniques in the past decades, such as radial probe-endobronchial ultrasonography (RP-EBUS), virtual bronchoscopy navigation (VBN), electromagnetic navigation bronchoscopy (ENB), bronchoscopic transparenchymal nodule access (BTPNA), and robotic-assisted bronchoscopy. However, these techniques also have their own limitations. In this review, we would like to introduce the development of diagnostic techniques for PPLs, with a special focus on biopsy approaches and advanced guided bronchoscopy techniques by discussing their advantages, limitations, and future prospects.